The Influence of Procedural Justice, Organizational Trust, and Organizational Commitment on Work Engagement - Kurniawati, Erna; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the influence of five variables, namely procedural justice, organizational trust, organizational commitment, in assessing job crafting's impact on strengthening or weakening the relationship between procedural justice and work engagement. The research is analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with 200 respondents from Civil Servants in the Indonesian National Police (Polri). The results show that procedural justice has a positive effect on organizational trust, organizational commitment, and work engagement. Organizational commitment positively influences work engagement, and job crafting moderates the procedural justice variable's impact on work engagement. Keywords: Procedural Justice, Organizational Trust, Organizational Commitment, Work Engagement and Job Crafting